System for administering and monitoring hydroxychloroquine prophylaxis for COVID-19 in accordance with a national advisory: preliminary experience of a tertiary care institute in India. Issue 10 (3rd October 2021) - Kumar-M, Praveen; Mohindra, Ritin; Bhalla, Ashish; Shafiq, Nusrat; Suri, Vikas; Kumari, Deepa; Pandey, Avaneesh Kumar; Gupta, Ankur; Gupta, Parul Chawla; Patil, Amol; Kakkar, Ashish Kumar; Malhotra, Samir
ABSTRACT: Background: Hydroxychloroquine (HCQ) was one of the earliest drugs to be recommended for tackling the COVID-19 threat leading to its widespread usage. We provide preliminary findings of the system, established in a tertiary care academic center for the administration of HCQ prophylaxis to healthcare workers (HCW) based on Indian Council of Medical Research (ICMR) advisory. Methods: A dedicated clinical pharmacology and internal medicine team screened for contraindications, administered informed consent, maintained compliance and monitored for adverse events. Results: Among the 194 HCWs screened for ruling out contraindications for prophylaxis, 9 were excluded and 185 were initiated on HCQ. A total of 55 adverse events were seen in 38 (20.5%) HCWs out of which 70.9%, 29.1% were mild and moderate & none were severe. Before the completion of therapy, a total of 23 participants discontinued. Change in QTc interval on day 2 was 5 (IQR: −3.75, 11) ms and the end of week 1 was 15 ms (IQR: 2, 18). Out of the 5 HCW who turned positive for COVID-19, 2 were on HCQ. Conclusion: HCQ prophylaxis was found to be safe and well tolerated in HCW when administered after appropriate screening and with monitoring for adverse events.